Use of Bosentan in neonatal post cardiac surgery pulmonary hypertension - Pawar Ravindra; Kasar Pankaj; Garekar Swati; Kulkarni Snehal (Wolters Kluwer Medknow Publications, 2009)
We report the use of Bosentan in the post-operative period of a neonate with obstructed infradiaphragmatic total anomalous pulmonary venous connection and severe pulmonary arterial hypertension. To our knowledge, this is the first report of use of Bosentan in this situation.